Dificultades en la lactancia materna e introducción alimentaria en bebés de 0 a 8 meses de edad con fisura labio palatina, Trujillo 2023 - Villalobos Zúñiga, Fiorella Ivette (2024)
This research aims to understand the difficulties in breastfeeding and food introduction in babies from 0 to 8 months of age with cleft lip and palate, Trujillo 2023. It was based on the quantitative research approach, descriptive type, non-experimental design and cross-sectional, having had as a sample a total of 50 babies with cleft lip and palate. There were two data collection instruments, which were developed by the researchers to measure each of the variables, being applied to the mothers of the babies. Regarding the most relevant results, it was obtained that in relation to swallowing difficulties, it was found that babies choked and choked more frequently, caused by the escape of milk through the nose (72.90%) and lip clefts (71.40%) during lactation. And regarding food introduction, it is known that 60% of babies began their process at 6 months of age, and the most used method was the traditional one. And the main conclusion reached by the research was that the main difficulties with sucking were that 85.71% of mothers breastfed their babies resting them on their arms, which is not a position recommended by specialists because it is exposes the baby to choking; Likewise, 72.86% of the babies at the time of sucking had their lips open, making the breastfeeding process difficult, relating to the 71.43% who indicated that they did not latch the nipple, all of which caused the baby to gag..